Análisis de zonas con alta demanda hídrica en la ciudad de Guayaquil utilizando sistemas de información geográfica SIG - Minango Valverde, Liz Monserratt (2023)
The work analyzes the areas with high water demand in Guayaquil using Geographic Information Systems (GIS). The methodology included the collection of data on water resources and water demand in the city, with projections up to the year 2041. The integration of these data into the GIS made it possible to identify critical areas and propose sustainable water management strategies. The results revealed that the parishes of Tarqui Oeste and Pascuales Noroeste III have the highest water demand. It was suggested to implement advanced water management technologies, such as remote meter reading and automated distribution control. In addition, the demand for water shows a growing trend in all land uses, which highlights the importance of careful planning of the available resources. The reuse of treated wastewater was proposed as a solution to diversify the sources of supply. In conclusion, the use of GIS has been effective in addressing the challenges of high-water demand in Guayaquil, providing key information to make informed decisions in water management and guarantee a reliable and sustainable supply for the community. The implementation of advanced technologies and sustainable practices will be essential to achieve efficient and responsible water management in the city.